Household reverse logistics analysis using the SCOR model to improve home safety of the elderly in the municipality - Supawadee Putthinoi (2018)
Copyright © 2015 Inderscience Enterprises Ltd. As Thailand enters an ageing society, reverse logistics concerning unused household items by elderly people becomes a problem for the local community. Throughout their lifetime, elderly people usually collect or hoard things in their house, which can lead to the risk of accidents by falling. There is very poor reverse logistics of household items, such as unused charity donations, in developing countries. A suburban village in Thailand was selected as a problem model. This study focused on unused household items in houses of the elderly. Therefore, it aimed to introduce the SCOR model for assessing this reverse logistics problem. The retail suppliers in the community were placed into six categories; electrical store, furniture store, pharmacy, bookstore, supermarket and temple. The flow of household products was a direct line from retailers to end users. The SCOR process (PSMDR) elements of all suppliers did not support the reverse logistics activity for elderly customers. To list in formal language was good for the local community to enable a flow of reverse logistics, which should improve Thailand's ageing society.